Responding to Child Maltreatment: Comparison between School Social Work in Finland and Germany - Beck, Kathrin Franziska; Vornanen, Riitta (Journal of Comparative Social Work, 2019)
Child maltreatment is a major topic of concern in European countries. This article compares how Finnish and German school social workers (SSW) respond to child maltreatment (CM). For the purpose of this study, a case vignette was designed that implied multiple forms of CM, including child sexual abuse, the failure to provide a child with adequate nutrition and hygiene and exposure to violent environments. Semi-structured interviews were undertaken with eight SSW from Finland and Germany to examine their first reactions to the case, their professional approach and country-specific solutions. The transcribed interviews were subjected to content analysis. Concerning suspected child sexual abuse, the findings reveal that the Finnish SSW would inform the child protection services and the police directly after information regarding suspected maltreatment had been verified, whereas the German participants would seek professional advice and carry out a risk assessment. However, despite the fundamental differences between these approaches, both are in line with national legislation. Concerning the inadequate provision of nutrition, the findings reveal that German children are not provided with free school meals nationwide like Finnish children. Nonetheless, as this study shows, providing children with a free school lunch does not ensure that they are adequately provided for during the entire day. It is recommended children in both countries be provided with free school meals nationwide, to implement means-tested benefits for those who need greater support and to strengthen the education of SSW in the early identification of child neglect, in addition to fostering a holistic approach to treating clients.